Assessment of 5 Hz and 10 Hz GPS units for measuring athlete movement demands - Johnston, R. J.; Watsford, M. L.; Pine, M. J.; Spurrs, R. W.; Sporri, D. (International Journal of Performance Analysis in Sport, 2013)
This study aimed to assess the validity and inter-unit reliability of 5 Hz and 10 Hz global positioning system (GPS) units and determine the differences between these units as measures of team sport athlete movement demands. A team sport simulation circuit was completed by eight trained male participants to examine the following movement demands: total distance covered (TD), peak speed and the distance covered, time spent and number of efforts performed at different speed zones. Additionally, repeated high intensity efforts, player load and exertion index were investigated. The analysis using paired samples t-test and percentage typical error of measurement (%TEM) revealed that 10 Hz GPS units provided a valid and reliable measure of TD (p>0.05, %TEM=1.3). The 5 Hz units also displayed reliable measures of TD (%TEM=1.2). It was apparent that as the speed of movement increased, the level of GPS error increased for both 5 Hz and 10 Hz units (%TEM: 0-14%). The updates in GPS firmware and increased sampling rates have further improved the validity and inter-unit reliability of GPS. Consequently, practitioners can more confidently rely on the data obtained from current GPS units during training and matches, however, caution is required when measuring high speed movements.